2021
DOI: 10.1111/opn.12363
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ reflections on their educational preparation to work with older people

Abstract: Background Negative perceptions about working with older people within nursing contribute to the deficit of educators with expertise to teach student nurses, and nurses graduating ill‐equipped to work with the ageing population. The perceptions of nurses who have recently graduated from a nursing programme can provide insights into what they wished they knew about working with older people before they graduated. Methods A qualitative descriptive study design examined recently graduated registered nurses’ refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Still, students wanted to learn more about aging and expressed interest in web-based and/or simulated learning activities. In another study, newly graduated nurses likewise identified the need for web-based learning activities that enhance knowledge about working with older people [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, students wanted to learn more about aging and expressed interest in web-based and/or simulated learning activities. In another study, newly graduated nurses likewise identified the need for web-based learning activities that enhance knowledge about working with older people [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preview literature also emphasized the importance of educational programs of making the advanced knowledge and skills of RNs involved in caring for older adults, due to the complexity and prevalence of the aging population in nursing practice. 40 , 41 To cope with the continuing shortage of RNs educated to care for older adults, competency-based education programs both at Bachelor’s and Master’s level had been developed in the USA and other countries. 42 , 43 However, in China, the development of geriatric care is relatively late and there is no established framework or standards for gerontological nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…It is curious that participants viewed the higher acuity areas as those serving younger people, since older people are the most common demographic in most types of healthcare settings (CIHI, 2011;HSCI, 2015). In another study, new graduates reported that they did not realise that the majority of the people they would be looking after would be older, nor did they realise the complexity of the older population until they graduated and started working (Dahlke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%